(untitled) (Literary Voice, 2023)
Ecological concerns demand recognition at this point of the Anthropocene epoch. There is a grave threat that European imperialism has caused what Rob Nixon calls ‘slow-violence’ to the environment. Kai Cheng Thom’s, Fierce Femmes and Notorious Liars: A Dangerous Trans Girl’s Confabulous Memoir (2016) is a work that intermingles elements of magical realism, ecocriticism, trans literature and postcolonialism. Using Postcolonial Ecocriticism as a critical lens, this paper aims to uncover the link between colonization and the ecological crises. The use of magical realism as a literary technique is analyzed to highlight the ways in which this tool helps transgress rigid binaries. The paper attempts to point out the impact of colonization in erasing cultures, communities and biodiversity in order to find a better way forward.